Integration of crude-oil scheduling and refinery planning by Lagrangean Decomposition. (12th July 2020) - Yang, Haokun; Bernal, David E.; Franzoi, Robert E.; Engineer, Faramroze G.; Kwon, Kysang; Lee, Sechan; Grossmann, Ignacio E.
Abstract: In this work, a Mixed-Integer Nonlinear Programming (MINLP) modeling framework for integrating short-term Crude-oil Scheduling (CS) and mid-term Refinery Planning (RP) has been developed and effectively solved by a proposed Lagrangean Decomposition (LD) algorithm. The principles of this integration are based on the fact that both Crude-oil Scheduling and Refinery Planning have their economic net values as their objectives, and that they are physically linked by Crude Distillation Units (CDUs). A multi-scale approach is proposed in the framework to aggregate continuous- and discrete-time formulations in CS and RP, respectively. Compared to hierarchically solving the non-integrated CS and RP, computational results show significant improvement regarding the economic objective values. Moreover, the proposed LD approach requires less CPU time converging to a small (1%-5%) optimality gap when compared to the monolithic approach using state-of-the-art MINLP solvers.